Synthesis, anti-bacterial and anti-fungal activities of some novel Schiff bases containing 2,4-disubstituted thiazole ring - Bharti S.K.; Nath G.; Tilak R.; Singh S.K. (My University, 2025)
A series of arylidene-2-(4-(4-methoxy/bromophenyl) thiazol-2-yl) hydrazines (4a-z) and 1-(4-(4-methoxy/bromophenyl) thiazol-2-yl)-2-cyclohexylidene/cyclopentylidene hydrazines (5a-b/6a-b) were synthesized, characterized and screened for their antimicrobial activities. The structures of synthesized compounds were established by spectroscopic (FT-IR, 1H NMR, 13C NMR, Mass) and elemental analyses. Both the anti-bacterial and anti-fungal activities with MIC values of compounds were evaluated. The results of anti-bacterial screening reveal that among all the compounds screened eight compounds showed moderate to good anti-bacterial activity while ten of the newly synthesized compounds displayed good to excellent anti-fungal activity. Among the tested compounds, the most effective compounds with MIC value in the range of 6.25-25 μg/ml are 4a, 4n, 4z, 5a, 5b, 6a and 6b against three fungal strains viz. Candida albicans, Cryptococcus neoformans and Aspergillus flavus. © 2009 Elsevier Masson SAS. All rights reserved.